Probing the Atmospheric Precipitable Water Vapor with SOFIA, Part I, Measurements of the Water Vapor Overburden with FIFI-LS. (13th April 2021) - Fischer, C.; Iserlohe, C.; Vacca, W.; Fadda, D.; Colditz, S.; Fischer, N.; Krabbe, A.
Abstract: We report on the measurements of telluric water vapor made with the instrument FIFI-LS on SOFIA. Since November 2018, FIFI-LS has measured the water vapor overburden with the same measurement setup on each science flight with about 10 data points throughout the flight. This created a large sample of 469 measurements at different locations, flight altitudes and seasons. The paper describes the measurement principle in detail and provides some trend analysis on the 3 parameters. This presents the first systematic analysis with SOFIA based on in situ observations.